Pengaruh Audit, Tata Kelola Desa, Value for Money, dan Sikap Moral terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa - Ninda Tiara Sondy; Yulita Zanaria; Angga Kurniawan (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the influence of audits, village governance, value for money, and moral attitudes on fraud prevention efforts in village fund management in Karya Jitu Mukti Village, Tulang Bawang Regency. The research method used was a quantitative survey approach. Primary data were collected through questionnaires and interviews with 33 respondents. The analysis technique used was multiple linear regression analysis with the help of SPSS 26 software. The results showed that all four independent variables simultaneously had a significant effect on fraud prevention efforts. However, only village governance, value for money, and moral attitudes had a positive effect. The audit variable had no positive effect on fraud prevention. Based on these results, it can be concluded that good governance, the application of value for money principles, and a high moral attitude are key factors in preventing fraud at the village level. Therefore, strengthening governance and improving the ethics and professionalism of village officials is necessary to create a transparent village fund management system